Stylet-driven Leads or Lumenless Leads for Conduction System Pacing - Óscar Cano; Jan De Pooter; Francesco Zanon (Arrhythmia & Electrophysiology Review)
Stylet-driven leads have been recently introduced for conduction system pacing, while most of the previous experience has been obtained with lumenless leads. Design and structural characteristics of both lead types are significantly different, resulting in different implant techniques and independent learning curves. Lead performance appears to be comparable, whereas data on direct comparison of clinical outcomes are scarce. Currently, there are no specific clinical scenarios favouring the use of one lead type over another and the decision should rely on the individual experience of the implanter.